Njavara rice (Oryza sativa Linn.) bran oil exerts anti-inflammatory effects through regulation of Notch-mediated T-cell receptor (TCR) activation in experimentally induced atherosclerosis: Rice bran oil exerts anti-inflammatory effects - Lal preethi SS,; Sabu, Vidya; Helen, Antony (Cellular and Molecular Biology, 2022)
This study elucidated the molecular mechanism of the notch pathway in vascular health and the role of NjRBO as a nutraceutical for the modulation of notch-mediated CD4+ Tcell activation in atherosclerotic rats. In this study, male Sprague–Dawley rats weighing 150–200g given standard diet formula were used. After the study duration of 60 days, in order to determine the nutraceutical effects of NjRBO, we sought to study the effects of treatment with NjRBO on notch pathway components in isolated splenic CD4+ T lymphocytes. In the present study, Western blot analysis revealed that upon high-fat diet supplementation resulted in T cell activation evidenced by increased CD28 co-receptor and CD25 marker expressions. In consistent with the above findings, we analyzed the mRNA expression pattern of Notch1, cleaved notch fragment, Notch-11C and Hes1, which showed a consistent up-regulation upon T-cell activation. Immunofluorescence assay also revealed an increase in Notch 1 receptor expression. Up-regulation in the expression of TCR-activated signalosome complexes or CBM complex in the diseased showed an increase indicating that Carma1-Bcl10-Malt1 (CBM) is a crucial event for T- cell receptor-induced NF-κB activation. Additionally, NF-қB translocation was enhanced in causing a concomitant alteration in Th1, Th2 transcription factors, T-bet, GATA-3 and its respective cytokines, IFN-γ and IL-4. Accordingly, we present evidence that Notch-regulated TCR-mediated activation of CD4+T-cell components was altered by NjRBO treatment, thereby revealing a novel role for the same in controlling TCR-mediated activation and inflammatory milieu.